PRELIMINARY STUDY OF ALTERED TERTIARY VOLCANICLASTIC ROCKS IN THE AREA OF ASPROULA , ΝΕΑ SANTA, RODOPI PERFECTURE, THRACE, NE GREECE - Μάραντος Ι.; Κοσιάρης Γ.; Καραντάση Σ.; Περδικάτσης Β.; Χρηστίδης Γ. (Bulletin of the Geological Society of Greece, 2004)
The area of Asproula is part of the Tertiary volcanosedimentary basin of Komotini, West Thrace. The geological structure of the area comprises metamorphic rocks of the Rhodope zone and Tertiary volcano-sedimentary rocks. The Tertiary sequence consists of three units: a) the lower unit, in contact with metamorphic rocks comprises sandstones-siltstones b) a unit, which comprises andesitic tuffs and c) a highe: unit consisting of dacitic-rhyodacitic volcaniclastics alternated with tuffites, siltstones, sandstones and marls forming a sequence about 150m thick. The acid volcaniclastics have been altered to clay minerals (mixed layer l-S, kaolinite, ), analcime, albite, and mordenite. The andesitic tuffs are slightly altered to smectite. Moreover in the andesitic tuffs laumontite and scolecite have formed along faults . According to the distribution of characteristic alteration minerals a zonation of alteration has been distinguished. Hence, the lower part of dacitic- ryodacitic tuffs has been altered to analcime + mixed layer l-S + quartz or albite + l-S + quartz, whereas in the upper part the volcaniclastics have been altered to kaolinite or mordenite. In the upper part of the dacitic-rhyodacitic sequence mordenite occurs in distinct thin pyroclastic flows (<5m thickness). The mode of succession of the mordenitic-kaolinitic alteration in the upper parts of the volcaniclastic sequence suggests rapid change in the chemistry of the mineral forming fluids. It is possible that temperature controlled the formation of mordenite. The presence of R1 ordered mixed layer l-S throughout the stratigraphie sequence suggests that the temperature during alteration exceeded 90° C. Moreover, the appearance of neo-formed albite in the lower part of the succession suggests that the temperature during alteration exceeded 120° C, in the lower parts of the formation.